Associations of the Healthy Beverage Index and the risk of colorectal cancer: a case-control study - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Mundher Kadem; Irfan Ahmad; Ahmed Hjazi (Frontiers in Nutrition)
BackgroundColorectal cancer (CRC) remains one of the leading causes of cancer-related morbidity and mortality worldwide. Emerging evidence suggests that dietary patterns can significantly influence CRC risk, with beverages playing a critical role. The Healthy Beverage Index (HBI) is a tool to assess the healthfulness of beverage consumption, yet its relationship with colorectal cancer risk has not been extensively studied.MethodsA total of 250 participants diagnosed with colorectal cancer and 250 age- and sex-matched control subjects were recruited for the study. Beverage intake was assessed using a validated dietary questionnaire, and HBI scores were calculated to reflect the quality of beverage consumption. Logistic regression analyses were performed to examine the association between HBI scores and colorectal cancer risk, controlling for potential confounders such as energy intake, physical activity, family history of cancer, and other lifestyle factors were assessed.ResultsThe case group had an average age of 48.91 years and BMI of 29.61, while the control group averaged 47.13 years and 29.07 BMI. CRC patients had a higher waist circumference (p < 0.05) and lower vitamin D intake and HBI scores than controls (p < 0.05). Those in the highest HBI quartile consumed more nutrients compared to the lowest (p < 0.05). Higher HBI scores correlated with increased physical activity. The highest HBI quartile significantly reduced CRC odds (OR: 0.28; 95% CI: 0.19–0.51), remaining significant after adjustments (OR: 0.43; 95% CI: 0.25–0.76).ConclusionThe HBI is inversely associated with the risk of colorectal cancer, suggesting that improvements in beverage choices may serve as an effective dietary strategy for CRC prevention. These results underscore the critical role of beverage consumption in dietary assessments and cancer risk management, warranting further examination in prospective studies.